A New Frontier in Relations between Türkiye and Turkic Republics: Cooperation in Defense Industry (Халықаралық қатынастар және халықаралық құқық сериясы, 2024)
In the post-Soviet era, Türkiye has been steadfast in strengthening its relations with newly independent Central Asian and Caucasian countries. These relationships initially encompassed various fields, including economics, culture, and education, but evolved towards energy cooperation and international initiatives in the 2000s. The 2010s witnessed the emergence of platforms like the Organization of Turkic States (OTS), Parliamentary Assembly of Turkic-speaking Countries (TÜRKPA), and International Organization of Turkic Culture (TÜRKSOY), fostering unity among Turkic nations. The defense and military sectors became focal points of collaboration. Türkiye has played a pivotal role in this, achieving significant success in its defense industry, with domestic production rates reaching 80% by 2022. This paper explores the historical context and key developments in Türkiye's defense industry, emphasizing its role in shaping diplomatic relations with Turkic Republics. The study also highlights Türkiye's efforts to become a regional power, fostering stability and peace in its neighborhood while expanding its influence in the defense industry sector. Collaborations with countries like Kazakhstan, Azerbaijan, Uzbekistan, and Kyrgyzstan have led to the establishment of military agreements and partnerships. These developments reflect the strategic aspirations of Turkic nations to enhance their defense capabilities and industries, with exchange of expertise and experience in the global defense arena.Key words: security, Kazakhstan, Türkiye, Turkic Countries, defense industry, Organization of Turkic State.